Analisis Nilai Tambahdan Rantai Pasok Gabah di Kecamatan Glumpang Tiga Kabupaten Pidie Provinsi Aceh - Mustafa Kamal; Risnadi Irawan; HanifMuchdatulAyunda (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Grainis the dominant agricultural commodity in Province of Aceh, grainisal sovery vulnerable to inflation. So far, there is no supply chain and calculation of added value on grain commodities in Glumpang Tiga District, Pidie Regency, the community, especially farmer groups as the main actors in the supply chain, do not know the added value of the commodities they produce, they are only considered as grain producers. On the basis of these problems, this research was developed with the aim of knowing the grain supply chain network to become rice and knowing how much added value for farmers and other actors in the rice supply chain networkin Glumpang Tiga District, Pidie Regency. This research was conducted using survey method and primary and secondary data collection from respondents through interviews and questionnaires. The data collected were then analyzed for added value usıng.The results of the research obtained a specific description of the grain supply chain that takes place in the Glumpang Tiga sub-district of Pidie district along with the flow of information, financial flow, and product flow. And the research results show that the commodity of grain into rice has a positive value for farmers, harvesters, and millers. Farmers have an added value of Rp.1,056/Kg with an average amount of 4,833/Kg of grain production, while the miller, the final actor in this supply chain gets a surplus witha valueof 65% orRp.1,324/Kg of net profit.